Impact of Strategic Adaptations Due to COVID-19 Pandemic on a Capacity Building Program: Insights From a DRTB Program Under NTEP in India (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2022)
Introduction: India has experienced high burden of drug resistant tuberculosis, under par treatment success rate and very high loss to follow-up despite continuous efforts to develop evidence-based policy to treat DRTB patients. However, it is challenging to translate policies into practice. The goal of this program was to build capacity of the program staff for effective management of DRTB in public sector through workshops, capacity building exercises, creation and dissemination of information, education and communication materials.Methodology: The program was implemented in seven states; 11 state-level kick-off trainings were planned to reach 660 National TB Elimination Program staffs. Due to COVID-19 pandemic, on-field activities were replaced with virtual trainings with a set of 4-5 webinars per state. Pre and post training assessments were done to evaluate uptake of knowledge. Number of trainings conducted, staff trained and knowledge improvement were the indicators used to assess the outcome.Results: A total of 34 webinars were conducted on revised Programmatic Management of Drug- Resistant Tuberculosis guidelines and 3000 staff was trained. The program organized three times more training and five times more staff were trained. Although retention of participants and their attention was challenging, transition to virtual platform provided increased coverage and targeted outputs. Proportion of participants answering correctly in pre/post-training assessments, increased from 47% to 65%.Conclusion: Use of virtual trainings is an efficient high yielding method to build capacity of NTEP staff. Lessons learnt can help improve such interventions, benefit health programs and the end beneficiaries - the patients.